DO TYPES OF ORGANIZATIONAL CULTURE CORRELATE WITH THE JOB SATISFACTION?: A STUDY ON EMPLOYEES' PERCEPTION - Diajeng Puspa Arum Maharani; Firda Nadia Roshandi (Universitas Airlangga, 2019)
Background: The Orthopaedic and Traumatology Hospital had an increase in employee turnover of 1.39% from January to June 2012. It occurred due to high resignation and employee unsatisfaction. Thus, an organizational culture that consists of clan, hierarchy, market, and adhocracy becomes one of the determinant factors for employee turnover. Aims: This study aims to analyze the correlation between organizational culture and the employees' job satisfaction. Method: This study used descriptive quantitative with a cross-sectional design, and the data were analyzed with a correlation test. There were 52 employees as the data of this study. The instruments utilized were OCAI and JSS questionnaires. Results: Market-type organization correlated significantly with job satisfaction. Organizational culture type, such as clan-type organization, adhocracy-type organization, and the hierarchy-type organization did not correlate significantly with job satisfaction. The majority of employees perceived that the Orthopedic and Traumatology Hospital adopts a hierarchy-type organization orienting to regulation and leadership. On the other hand, they expected the hospital to apply clan-type organizations that concerned about teamwork and ownership. Conclusion: There is a correlation between the market-type organization and job satisfaction. Meanwhile, there is no correlation between the clan-type organization, adhocracy-type organization, hierarchy-type organization, and job satisfaction. The hospital should increase internal strength, such as teamwork, training, facilities, and policies that support work procedures and staff. Keywords: market, adhocracy, clan, hierarchy, employees' job satisfaction.